Role of Human Resource Management in Job Satisfaction of Employees: A Comparative Analysis in Public & Private Sector - Sweta, Dr (International Journal of Social Sciences and Management, 2015)
This study investigates the relationship between human resource management and employees’ job satisfaction in public and private undertakings. The results revealed a positive relationship between managers and employees’ job satisfaction. The analysis is based on a sample of 100 employees which were randomly chosen from both the sectors. The happier people are within their job, the more satisfied they are said to be. This paper surveys both the sectors in most of the aspects of analysis. However both sectors have their own pros and cons which will be made clear while evaluating job-satisfaction levels among the employees of both the sector. And given that the reward system in the public sector systematically differs from that of the private sector (in terms of pay, benefits, and psychic value), it seems likely that studies of satisfaction levels among private-sector employees may not be applicable to public-sector employees. Int. J. Soc. Sci. Manage. Vol-2, issue-3: 263-266 DOI: http://dx.doi.org/10.3126/ijssm.v2i3.12751